2017
DOI: 10.1007/s00775-017-1452-5
|View full text |Cite
|
Sign up to set email alerts
|

Functional disruption of peroxiredoxin by bismuth antiulcer drugs attenuates Helicobacter pylori survival

Abstract: Bismuth drugs have been used clinically to treat infections from Helicobacter pylori, a pathogen that is strongly related to gastrointestinal diseases even stomach cancer. Despite extensive studies, the mechanisms of action of bismuth drugs are not fully understood. Alkyl hydroperoxide reductase subunit C (AhpC) is the most abundant 2-cysteine peroxiredoxin, crucial for H. pylori survival in the host by defense of oxidative stress. Herein we show that a Bi(III) antiulcer drug (CBS) binds to the highly conserve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 48 publications
2
10
0
Order By: Relevance
“… 71 We have demonstrated in previous studies that bismuth impairs the oxidative defense systems in H. pylori by binding and functionally disrupting key enzymes such as catalase, arginase and peroxiredoxin. 10 , 72 Herein, we observed at the transcriptome level the down-regulation of genes tpx , trxA and trxB encoding key antioxidant enzymes, 73 and genes mutS and recA encoding DNA repair enzymes, 74 , 75 further corroborated the reduced oxidative defense ability of H. pylori upon CBS treatment. Moreover, we detected elevated levels of intracellular ROS induced by CBS ( Fig.…”
Section: Discussionsupporting
confidence: 59%
“… 71 We have demonstrated in previous studies that bismuth impairs the oxidative defense systems in H. pylori by binding and functionally disrupting key enzymes such as catalase, arginase and peroxiredoxin. 10 , 72 Herein, we observed at the transcriptome level the down-regulation of genes tpx , trxA and trxB encoding key antioxidant enzymes, 73 and genes mutS and recA encoding DNA repair enzymes, 74 , 75 further corroborated the reduced oxidative defense ability of H. pylori upon CBS treatment. Moreover, we detected elevated levels of intracellular ROS induced by CBS ( Fig.…”
Section: Discussionsupporting
confidence: 59%
“…It has been reported that sodB mutants were more sensitive to oxidative stress and defective to colonize the mouse stomach (Seyler et al ). Two peroxiredoxins (HP1563, HP0390) were upregulated in this study, which were crucial for H. pylori survival in the host by defence of oxidative stress (Chang et al ). A recent study suggested that urease can protect H. pylori against oxidative damage via Met residue‐mediated quenching of harmful oxidants (Schmalstig et al ).…”
Section: Discussionmentioning
confidence: 65%
“…It has indicated that Bi enhanced the level of alkyl hydroperoxide reductase subunit C (AhpC) which is the most abundant 2‐cysteine peroxiredoxin in decomposing the exogenous reactive oxygen species (ROS) contributes to anti‐bacterium mechanisms [30]. Therefore, induction the ROS or OS damages are important mechanisms against bacterium especially H. Pylori might be accelerated by Bi compounds.…”
Section: Discussionmentioning
confidence: 99%